Translocation of Nuphar lutea (L.) Sibth. & Sm. from the A2 road near Nowy Tomyśl (Poland) into alternative sites - Borysiak, Anna; Borysiak, Janina; Joniak, Tomasz; Nagengast, Barbara (Biodiversity: Research and Conservation, 2011)
A translocation of Nuphar lutea (L.) Sibth. & Sm. was made from its primary location in Prądówka, situated in the path of the construction site of the A2 motorway, into replacement biotopes. All rhizomes were taken out of the water and used to prepare cuttings. These were divided into three approximately homogeneous groups. Each group was introduced into different replacement water bodies with environmental conditions that resembled those of the biotope in the Prądówka site. Two of the water bodies were fish ponds. A third was a so called ‘ecological water body’ (settling pond, settling basin) that collected fall effluents delivered from the surface of motorway. The results of the examination of the physical-chemical features of water and bottom sediments from the Prądówka peat pit, two fish ponds and four settling basins are presented in the article. Biological and autecological features of the species Nuphar lutea, which are significant from the aspect of the growth of the seedlings within the alternative sites, have been discussed. A year after translocation it was observed that in the case of fish ponds, 83% and 75% of the introduced plants survived, while in the settling basin only 50%. A conservation project was undertaken by the investor in order to compensate for the negative effects of the A2 motorway within the area of the European Ecological Natura 2000 Network.